2018
DOI: 10.1002/cam4.1844
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell histiocytosis in adults is associated with a high prevalence of hematologic and solid malignancies

Abstract: BackgroundLangerhans cell histiocytosis (LCH) is a rare disorder of histiocyte proliferation. Previous case studies suggest a higher prevalence of hematologic and solid malignancies among LCH patients, possibly due to treatment with tumorigenic agents such as etoposide. We report the first large, single‐institution experience of adult LCH patients with additional malignancies to study the characteristics of these patients.MethodsWe identified 132 consecutive patients >18 years of age with histologically confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 22 publications
0
31
0
1
Order By: Relevance
“…Conversely, transformation of antecedent haematological malignancies to secondary histiocytic neoplasms may also occur [17,18]. In the 1990s, the LCH‐Malignancy Study Group of the Histiocyte Society already reported recurrent associations between LCH and leukaemia or lymphoma [19,20], which were confirmed in later studies [21,22]. Likewise, a high prevalence of haematological malignancies was also observed in adults with ECD [23] or HS [24].…”
Section: Introductionmentioning
confidence: 96%
“…Conversely, transformation of antecedent haematological malignancies to secondary histiocytic neoplasms may also occur [17,18]. In the 1990s, the LCH‐Malignancy Study Group of the Histiocyte Society already reported recurrent associations between LCH and leukaemia or lymphoma [19,20], which were confirmed in later studies [21,22]. Likewise, a high prevalence of haematological malignancies was also observed in adults with ECD [23] or HS [24].…”
Section: Introductionmentioning
confidence: 96%
“…However, it was typically associated with concomitant metastasis in the same lymph node. 33,34,36 In fact, this will make the diagnosis more challenging, as cells seen in LCH can mimic those seen in PTC and malignant melanoma; moreover, both malignant melanoma and LCH show S100 protein-positive reaction. In both of our cases, there was no evidence of metastases in lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies have shown a higher prevalence of hematological and solid malignancies among LCH patients. 35,36 A study by Jennifer Ma et al 36 of adult LCH patients found an exceptionally high number of additional malignancies. The identified malignancies were diagnosed either earlier or at the same time as a diagnosis of LCH, indicating that the cause of malignancies is not secondary to LCH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The chemotherapy for LCH and genetic predisposition may be explanations. Previously, 27 such cases have been reported [1], and lymphomas, solid tumors, and other hematologic malignancies have been associated with chemotherapy for LCH [2]. Most patients develop AML at least 2 years (mean: 5.5 years) after LCH treatment [3].…”
Section: To the Editormentioning
confidence: 99%
“…A safe dose of etoposide does not truly exist; between 2 and 20 years after exposure to etoposide, 1%-5% of patients may develop t-AML [5]. Etoposide-associated AML has been described after its usage for a wide spectrum of diseases, including non-Hodgkin lymphoma [6], acute lymphoblastic leukemia [7], solid tumors [2], and hemophagocytic lymphohistiocytosis [5]. The cytogenetic abnormalities of t-AML reported in patients with LCH include t(15;17), 11q23, +16, and +21 [8,9,10].…”
Section: To the Editormentioning
confidence: 99%